FAKTOR DETERMINAN KEJADIAN PNEUMONIA PADA ANAK - Mellysa Wulandari Tasripin; Andi Silfiana; Amos Lellu; Chrecencya Nirmalarumsari (Ensiklopedia Research and Community Service Review, 2026)
Pneumonia is a serious health problem and a leading cause of death among children under five years of age (toddlers) worldwide. Based on the results of a preliminary study conducted at the Jagakarsa Community Health Center, it was found that the number of pneumonia cases among toddlers has shown an upward trend over the past two years. The objective of this study was to identify the determinants of pneumonia incidence in children. A case-control study design was used in this research. The study was conducted in the service area of the Jagakarsa Community Health Center. The study was carried out in April 2025. The study population consisted of all infants registered at the Jagakarsa Community Health Center. The sample comprised 27 case respondents and 27 control respondents. Simple random sampling was used. The research instrument was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results indicated an association between smoking behavior (p-value: 0.005) and exclusive breastfeeding (p-value: 0.021) with the incidence of pneumonia in children. It is recommended that parents take several measures, such as ensuring routine immunizations, regular check-ups at the community health center or local health post, and seeking immediate medical attention if their child becomes ill. Keywords: Exclusive Breastfeeding, Children, Pneumonia.